Effects of training modality on audio-visual perception of nonnaitve speech contrasts - Wang, Yue; Behane, Dawn; Jiang, Haisheng (Canadian Acoustics, 2008)
The effects of training modality on audio-visual perception of nonnative speech contrasts was investigated. Forty-four young adult mandarin Chinese natives with less than five years’ residency in Canada participated in the study. Pre/posttest stimuli were recorded of an adult male speaker of Canadian English. The stimuli were based on 18 English CV syllables having a fricative followed by a vowel. The fricatives differed in place of articulation and the participants task was to identify the fricatives while listening to the sounds over a headset, or viewing the speaker mouth movements on the screen, or both. the perceptual training program followed the high variability procedure demonstrated to be highly effective in auditory perception training. The results revealed a noticeable effect of training modality, where the extent of post-training improvement was consistent with the type of training.